2019
DOI: 10.5847/wjem.j.1920-8642.2019.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical knowledge and psychomotor skill acquisition of basic life support training programme among secondary school students

Abstract: BACKGROUND: The aim of the study is to evaluate the theoretical knowledge and psychomotor skill acquisition of basic life support (BLS) by a group of secondary school students in Nigeria pre and post BLS training. METHODS: This was quasi-experimental study design with 210 participants. They were taught on adult BLS and all the participants practiced BLS on a Resusci-Anne manikin immediately after the training. Data were collected using American Heart Association (AHA) structured questionnaire and psychomotor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 24 publications
0
3
0
2
Order By: Relevance
“…Assim, apesar de serem evidentes os benefícios de intervenções que utilizam de diferentes estratégias de ensino, o desenvolvimento de treinamento teórico colaborou para a apreensão de conteúdo, melhorando a capacidade cognitiva dos participantes. Mesmo que a intervenção aplicada não tenha apresentado aumento na quantidade de acertos em todos os itens abordados, o incremento dos números de itens apreendidos na análise dos módulos do curso e em tópicos específicos apontam que a aula teórica foi uma importante estratégia de ensino e aprendizagem, semelhante a outros estudos, que também têm apontado para melhorias no conhecimento apreendido (Miotto et al, 2010;Moraes et al, 2017;Gabriel & Aluko, 2019;Tony et al, 2020).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Assim, apesar de serem evidentes os benefícios de intervenções que utilizam de diferentes estratégias de ensino, o desenvolvimento de treinamento teórico colaborou para a apreensão de conteúdo, melhorando a capacidade cognitiva dos participantes. Mesmo que a intervenção aplicada não tenha apresentado aumento na quantidade de acertos em todos os itens abordados, o incremento dos números de itens apreendidos na análise dos módulos do curso e em tópicos específicos apontam que a aula teórica foi uma importante estratégia de ensino e aprendizagem, semelhante a outros estudos, que também têm apontado para melhorias no conhecimento apreendido (Miotto et al, 2010;Moraes et al, 2017;Gabriel & Aluko, 2019;Tony et al, 2020).…”
Section: Discussionunclassified
“…O aumento das doenças cardiovasculares (DCV) representa um grave problema de saúde pública em todo o mundo, em especial para os países de baixa e média renda, sendo um importante desafio para a rede de assistência em saúde atual (Gabriel & Aluko, 2019). Em 2016, estima-se que mundialmente tenha ocorrido mais de 17,9 milhões de óbitos; aproximadamente um terço destes números foi ocasionado por DCV que, na maioria das vezes, evoluiu em parada cardiorrespiratória (PCR) (OMS, 2017).…”
Section: Introductionunclassified
“…We have found no publications reporting actual bystander resuscitation rates in Nigeria. Several studies from Nigeria showed null previous training and poor BLS knowledge among secondary school students [23] and school teachers, [24] as well as inadequate knowledge and sparse training in CPR among the healthcare professionals. [25,26] Additional studies are required to investigate the existing proportions of the general public that have undergone BLS training in India and Nigeria, as well as to understand the populations' attitude, willingness and barriers to get trained in CPR.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Another important way to boost the rates of bystander resuscitation is to include compulsory CPR training into school curriculum, [1] that hopefully will be achieved in the UK by the year of 2020, [27] but is yet to attain success in India [28] and Nigeria. [23,24]…”
Section: Discussionmentioning
confidence: 99%
“…It has a mixture of abilities including mouth-to-mouth breathing to support ventilation and chest compressions to normalize blood circulation to the brain and vital organs, called (CPR). BLS may be a basic and very effective method that allows anyone to help assist maintain life, soon after heart attack [5].…”
Section: Introductionmentioning
confidence: 99%